2017
DOI: 10.1159/000458469
|View full text |Cite
|
Sign up to set email alerts
|

Xp22.31 Microdeletion due to Microhomology-Mediated Break-Induced Replication in a Boy with Contiguous Gene Deletion Syndrome

Abstract: The Xp22.31 region is characterized by a low frequency of interspersed repeats and a low GC content. Submicroscopic deletions at Xp22.31 involving STS and ANOS1 (alias KAL1) underlie X-linked ichthyosis and Kallmann syndrome, respectively. Of the known microdeletions at Xp22.31, a common approximately 1.5-Mb deletion encompassing STS was ascribed to nonallelic homologous recombination, while 2 ANOS1-containing deletions were attributed to nonhomologous end-joining. However, the genomic bases of other microdele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Although both patients had NLGN4X and VCX-A deletions, neither had speech defects, intellectual disability, autism, or social disorders. Previous observations also indicated that the deletion of NLGN4X may be associated with normal mental development (Khelifa et al, 2013;Nagai et al, 2017). VCX-A deletion is associated with XLI (Van Esch et al, 2005;Cuevas-Covarrubias and González-Huerta, 2008), poor sperm production, and sexual development abnormalities (Zou et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although both patients had NLGN4X and VCX-A deletions, neither had speech defects, intellectual disability, autism, or social disorders. Previous observations also indicated that the deletion of NLGN4X may be associated with normal mental development (Khelifa et al, 2013;Nagai et al, 2017). VCX-A deletion is associated with XLI (Van Esch et al, 2005;Cuevas-Covarrubias and González-Huerta, 2008), poor sperm production, and sexual development abnormalities (Zou et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Another patient who had a deletion of NLGN4X demonstrated normal mental development (Khelifa et al, 2013). Renal agenesis occurred in 8 of the 20 patients, which may be caused by an ANOS1 deletion (Martul et al, 1995;Krishnamurthy et al, 2007;Macarov et al, 2007;Trevisson et al, 2015;Xu et al, 2015;Nagai et al, 2017). Previous literature also noted that patients with KS harboring a deletion in Xp22.3 were more likely to exhibit renal agenesis (Kirk et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to small sample size, we cannot robustly ascertain whether a low GC-content sequence would be more vulnerable to DNA breakpoints than a high GC-content sequence. However, utilizing GC content and reciprocal sub-chromosomal arm gain-loss complementary as a reference may prove a more e cient tool in distinguishing real DNA segments from NGS data noise generated from a sample of DNA in SCM [19,32] .…”
Section: Resultsmentioning
confidence: 99%
“…STS deficiency results in accumulation of cholesterol sulfate in the outer layers of the skin, inducing intercellular cohesion and scaling in XLI [ 13 ]. Up to 90% of the XLI patients presented complete deletion of the entire STS gene, and deletions could even extend to neighboring genes sometimes, leading to continuous gene syndromes [ 6 , 14 ]. Less frequent point mutations have been reported as well [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%